Ways to expand network marketing and e-commerce in the wholesale of medicines - Musayeva Shoira Azimovna; Usmanov Farzod Shokhrukhovich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
This article discusses the creation of targeted proposals to understand customers and their needs in the sale of drugs, the formation of strategies for working with clusters, the development of partnerships for revenue.